2018
DOI: 10.1080/15384101.2018.1509636
|View full text |Cite
|
Sign up to set email alerts
|

TLR-4/microRNA-125a/NF-κB signaling modulates the immune response to Mycobacterium tuberculosis infection

Abstract: Tuberculosis (TB), caused by Mycobacterium tuberculosis, could lead to kinds of clinical disorders and remains a leading global health problem, resulting in great morbidity and mortality worldwide. Previous studies have firmly demonstrated that M. tuberculosis (M.tb) has evolved to utilize different mechanisms to evade or attenuate the host immune response, such as regulation of immune-related genes by modulation of miRNAs of host or bacteria. However, the knowledge of functions of miRNAs during M.tb infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…28 An experiment reveals that miR-125a negative regulates NF-kB pathway via directly targeting TRAF6, reducing the inflammatory cytokines expressions in mycobacterium tuberculosis infection. 19 It is also reported that miR-125a mimic ameliorates the effect of IL-6 on promoting the neutrophil chemoattractant expression both in vitro and in vivo in lung inflammation. 17 Another experiment reports that miR-125a targets effector programs and subsequently stabilizes the immune homeostasis mediated by Tregs.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…28 An experiment reveals that miR-125a negative regulates NF-kB pathway via directly targeting TRAF6, reducing the inflammatory cytokines expressions in mycobacterium tuberculosis infection. 19 It is also reported that miR-125a mimic ameliorates the effect of IL-6 on promoting the neutrophil chemoattractant expression both in vitro and in vivo in lung inflammation. 17 Another experiment reports that miR-125a targets effector programs and subsequently stabilizes the immune homeostasis mediated by Tregs.…”
Section: Discussionmentioning
confidence: 97%
“…miR‐125a belongs to the miR‐125 family, and the family includes miR‐125a, miR‐125b1 and miR‐126b2 . An experiment reveals that miR‐125a negative regulates NF‐kB pathway via directly targeting TRAF6, reducing the inflammatory cytokines expressions in mycobacterium tuberculosis infection . It is also reported that miR‐125a mimic ameliorates the effect of IL‐6 on promoting the neutrophil chemoattractant expression both in vitro and in vivo in lung inflammation .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many potential targets were predicted, and TRAF6 was selected from these predicted targets for further validation, as TRAF6 has been reported for its role in M tb infection. 20 The bioinformatics analysis showed that TRAF6 was one of the miR-140targeted genes, and the complementary sequences between miR-140 and TRAF6 3′UTR were shown in Figure 5A…”
Section: Mir-140 Suppressed Traf6 Expression Via Targeting the 3'utrmentioning
confidence: 99%